Analysis of thermal stress intensity factors for edge cracked bimaterial system - Hrairi, Meftah; Ali, Arafath; Rizk, Abd El-Fattah (Trans Tech Publications, Switzerland, 2012)
The thermo elastic edge-cracking problem in bimaterial systems subjected to convective heating is considered. The medium is assumed to be insulated on one surface and exposed to sudden convective heating on another surface containing the edge crack. Superposition and uncoupled quasi-static thermoelasticity principles are adopted to formulate the problem. Thermal stress distribution and stress intensity factor values had been determined using the finite element software ANSYS for two different bi-material systems containing edge crack normal to the interface.